2021
DOI: 10.3390/polym13040510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Antibacterial Efficacy and Biocompatibility of PAN Nanofibers Loaded with Diclofenac Sodium Salt

Abstract: Side effects of the drugs’ oral administration led us to examine the possibility of using diclofenac sodium (DLF) in a polymeric drug delivery system based on electrospun polyacrylonitrile (PAN) nanofibers, which can be produced cost-effectively and with good applicability for transdermal treatments. The inclusion of DLF in PAN nanofibers increased the nanofiber diameter from ~200 nm to ~500 nm. This increase can be attributed to the increase in the spinning solution viscosity. FTIR spectra confirm the entrapm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 42 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…In this study, the antimicrobial activity of the electrospun pure PCL and DSS-loaded PCL mats was tested against S. aureus and E. coli by the contact method according to ISO 22196:2011. The selected bacterial strains are the most common bacteria that cause soft tissue infections that delay wound healing [76,77]. S. aureus most often causes skin infections [78], while E. coli is considered the primary source of burn wound infections [79].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the antimicrobial activity of the electrospun pure PCL and DSS-loaded PCL mats was tested against S. aureus and E. coli by the contact method according to ISO 22196:2011. The selected bacterial strains are the most common bacteria that cause soft tissue infections that delay wound healing [76,77]. S. aureus most often causes skin infections [78], while E. coli is considered the primary source of burn wound infections [79].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biological molecules can be incorporated into the polymer matrix 12 . Because of its outstanding properties such as chemical stability, light resistance, non-toxicity, electrospinning, and mechanical elasticity, polyacrylonitrile (PAN) is a popular polymer for wound dressing 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of antibiotics to prevent infections is an effective solution, due to the occurrence of resistant pathogenic microorganisms and slower synthesis/isolation of new antibiotics, there is a need for alternative solutions [ 9 ]. Previous studies [ 23 , 24 , 25 , 26 ] have shown that diclofenac-incorporated formulations have antimicrobial activity, to some extent, against various bacterial strains. Since diclofenac primarily acts as an anti-inflammatory drug, which reduces post-injury pain, its additional advantage in wound treatment is its antibacterial property.…”
Section: Introductionmentioning
confidence: 99%